PLANT miRNAs: KEY PLAYERS IN INTER-KINGDOM AND INTRA-KINGDOM GENE REGULATION - SANGEETA SAXENA,; ASHISH KUMAR,; SUNIL G BABU, (International Journal of Pharma and Bio Sciences, 2014)
Micro RNAs (miRNAs) are a class of 21-24 nucleotide long single stranded, endogenous, non- coding RNAs involved mainly in post transcriptional gene silencing in animals and plants. Their role in the gene regulation of plant growth and development, biotic and abiotic stress responses, methylation is revealed and much more is expected by these tiny molecules. With each passing day a new insight about miRNAs and their explicit role in signaling, plant immunity and plant pathogen interactions are accumulating to the literature. In addition, the identification of miRNAs in plants and human secretions and their role in regulating the human genes are now reported. This observation leads to the speculation of therapeutic role of secretory miRNAs of such plants which exhibits medicinal value. Further, with proven evidences of their crucial role in cross kingdom gene regulation of several human genes many diseases can be treated by mere consumption of these plant miRNAs through food. In this review we have discussed about the significant role of plant miRNA in various biological system, speculating their potential use as therapeutics giving an altogether new direction to molecular biology research on these small RNA molecules.